Sustainability of motor training effects in older people with dementia - Zieschang, Tania; Oster, Peter; Hauer, Klaus (Journal of Alzheimer's disease, 2013)
Evidence for sustainability of motor training effects in people with dementia is lacking. To examine whether the substantial improvements in motor performance achieved through a three-month specialized, standardized motor training were sustained, the